(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Slyuta A. N. Pedagogical conditions of professional skills to students of environmental practices in the production process for use in their future activity. The paper summarizes the pedagogical conditions of professional skills to students of environmental practices in the production process for use in their future professional activity. The author draws attention to the need to improve the quality of pedagogical conditions of training of environmental specialists.